Analisis Implementasi Nilai Karakter Peduli Terhadap Penerapan Program SDGs Nomor 2 - Alifah, Rif’at NurAesy; T, Trimurtini (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In 2017, the Indonesian Government committed to participate in Global Engagement with the United Nations under the Sustainable Development Goals (SDG) through Presidential Decree of the Republic of Indonesia No. 59. Along with the Indonesian government's focus on implementing the Sustainable Development Goals, the country is also receiving a demographic bonus with an estimated productivity of 67%, which has great potential to advance the country as an implementer of national interests. At the same time, the Indonesian nation faces challenges and threats of national resistance originating from socio-political and economic conditions at the global, regional and national levels. This article examines the position of the SDGs on the global agenda, Indonesia's national interests in the SDGs, and their impact on national sustainability. In this article the author focuses on achieving SDGs Number 2. In this way, general health insurance must be taken. The SDGs are based on the idea that environmental and social justice. It must be made clear that all stakeholders and sectors must contribute to achieving the SDG goals. The government aims to improve the quality of health services by achieving sustainable progress, economic growth must be in line with the consideration of introducing social insurance programs to guarantee the health rights of the poor and disadvantaged.